The influence of social media usage and electronic word-of-mouth on Hot Wheels purchase intention in West Sumatra: The mediating role of brand equity - Kharisma Utama, Hafiz; Maulana, Arief (Marketing Management Studies, 2025)
Purpose- This study examines the influence of social media usage (SMU) and electronic word of mouth (eWOM) on purchase intentions for Hot Wheels diecast collectibles in West Sumatra, using brand equity (BE) as a mediating variable. Design/methodology/approach- An online survey was conducted, gathering data from 168 Hot Wheels collectors and enthusiasts in West Sumatera, Indonesia. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationships between variables. Findings- Results demonstrate that social media usage, electronic word of mouth, and brand equity each significantly influence consumers’ purchase intentions. Additionally, brand equity is found to be positively impacted by social media usage and electronic word of mouth. Finally, brand equity partially mediates the relationship between social media usage, electronic word of mouth, and purchase intentions for Hot Wheels.